2012
DOI: 10.1158/0008-5472.sabcs12-p5-18-11
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-18-11: Pharmacokinetics and exposure-efficacy relationship of trastuzumab emtansine in EMILIA, a phase 3 study of trastuzumab emtansine vs capecitabine and lapatinib in HER2-positive locally advanced or metastatic breast cancer

Abstract: Background: Trastuzumab emtansine (T-DM1) is an antibody-drug conjugate composed of trastuzumab (T), the cytotoxic agent DM1, and a stable thioether linker; it is being evaluated for the treatment (tx) of HER2-positive cancer. EMILIA is a randomized, multicenter, open-label phase 3 study assessing the efficacy and safety of T-DM1 vs capecitabine (X) and lapatinib (L) in pts with HER2-positive locally advanced or metastatic breast cancer (MBC) previously treated with T and a taxane. We report the pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Wang concluded that T-DM1 pharmacokinetics data were similar in previous phase II studies with historical data of single agent T-DM1 [40]. Furthermore, there was no significant exposure-efficacy relationship observed between T-DM1 AUC ( P  = 0.23 for PFS and P = 0.53 for OS) or DM1 Coax ( P  = 0.96 for PFS and P  = 0.34 for OS) and PFS or OS, respectively [40]. …”
Section: Her2 Overviewmentioning
confidence: 62%
“…Wang concluded that T-DM1 pharmacokinetics data were similar in previous phase II studies with historical data of single agent T-DM1 [40]. Furthermore, there was no significant exposure-efficacy relationship observed between T-DM1 AUC ( P  = 0.23 for PFS and P = 0.53 for OS) or DM1 Coax ( P  = 0.96 for PFS and P  = 0.34 for OS) and PFS or OS, respectively [40]. …”
Section: Her2 Overviewmentioning
confidence: 62%
“…T-DM1 was also examined for exposure-response relationships using data from Phase II and III clinical trials (including T-DM1 area under the curve [AUC], peak plasma concentration [C max ], minimum plasma concentration [C min ], trastuzumab AUC, and DM1 C max ) [28,32]. Analysis of the Phase III EMILIA study showed no clear trends between T-DM1 exposure (C max and AUC) and efficacy (progression-free survival [PFS]; overall survival [OS]; or response rate) [32].…”
Section: Clinical Pharmacologymentioning
confidence: 99%
“…Analysis of the Phase III EMILIA study showed no clear trends between T-DM1 exposure (C max and AUC) and efficacy (progression-free survival [PFS]; overall survival [OS]; or response rate) [32]. A slight trend was observed for improved OS by stratified T-DM1 C min quartiles, although with overlapping 95% confidence intervals.…”
Section: Clinical Pharmacologymentioning
confidence: 99%